Methodological considerations and cost to measure coverage of multisectoral nutrition interventions: Protocol for the One Nutrition Coverage Survey in Bangladesh - Manohar, Swetha; Nguyen, Phuong Hong; Neupane, Sumanta; Munos, Melinda Kay; Heidkamp, Rebecca; Banerjee, Archis; Pandya, Niharika; Kim, Sunny S. (BMJ, 2025)
Introduction Despite global commitments to eliminate malnutrition, over half the world’s population remains affected. Multisectoral nutrition interventions targeting both proximate and distal causes of malnutrition are essential across the lifespan. Yet, current data collection lacks comprehensive nutrition intervention coverage measures, risking inaccuracies in tracking progress. The One Nutrition Coverage Survey (ONCS) aims to test new and refined coverage measurement methods, assess coverage equity and guide integration into large-scale household surveys.